A Darwinian Pilgrim's Middle Progress. (10th December 2018) - Ruse, Michael
Abstract : Part two of three in an autobiographical series which retraces the most significant events, collaborations, and research results of Michael Ruse's 55-year-long career in the history and philosophy of science. In this article, Ruse's first forays into philosophy are intertwined with his growing interest in the history of science. The main topics summarized in this second installment are considered thematically as they developed: "design" as a Kuhnian paradigm in the history of evolutionary biology (from the early 1970s onwards); the involvement in the McLean v. Arkansas Board of Education 1981 legal case which saw the rise of neo-creationism as organized pressure group; the exploration of the science-religion relationship (mid-1980s to 1990s); the problem of free will and the critical confrontation with the New Atheism (early 2000s); the question of accommodationism and the identification of "organism" as the root metaphor of evolutionary biology (2010s).